1974
DOI: 10.1111/j.1432-1033.1974.tb03878.x
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Pre‐Steady‐State Kinetics of Oxidation of Benzyl Alcohols by Liver Alcohol Dehydrogenase

Abstract: 1. The oxidation of benzyl alcohols by liver alcohol dehydrogenase under conditions [S], $-[El, is a biphasic process with exponential rise to a steady state. The rate constants for the transient phase were determined by a curve-fitting procedure.2. A large isotope effect was obtained for p-methoxybenzyl alcohol, indicating that hydrogen transfer is rate-determining for the transient phase. Rate constants for the hydrogen transfer step, k3, were obtained for the various alcohols and correlated with the Hammett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Interpretation of Substituent Effects. Hardman et al (1974) and we have found small, negative p values (p+ = -0.2 to -0.4) for the oxidation of substituted benzyl alcohols. Furthermore, Blackwell and Hardman (1975) found a value of p* of -1.8 for a series of different primary alcohols.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Interpretation of Substituent Effects. Hardman et al (1974) and we have found small, negative p values (p+ = -0.2 to -0.4) for the oxidation of substituted benzyl alcohols. Furthermore, Blackwell and Hardman (1975) found a value of p* of -1.8 for a series of different primary alcohols.…”
Section: Discussionmentioning
confidence: 52%
“…The magnitudes of the isotope effects indicate that transfer of hydrogen in the ternary complexes is at least partially rate limiting in the steady-state turnover. Although the isotope effects are not large, they are the same as those obtained from transient kinetic studies with the liver enzyme (Hardman et al, 1974;McFarland and Bernhard, 1972;Jacobs et al, 1974) and almost as large as those obtained from steady-state studies with the yeast enzyme (Klinman, 1972(Klinman, , 1975. Given that transfer of hydrogen is at least partially rate limiting, the mechanism of hydroxybutyrimidylated enzyme acting on benzyl alcohol may not be a compulsory order, but rather a preferred order, mechanism, as was found previously for the native enzyme acting on secondary alcohols (Dalziel and Dickinson, 1966;Dalziel, 1975).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Funderburk & Jencks (1978) have recently discussed the imbalance in values of Bronsted a's and /3's, p values, and «-secondary isotope effects for the acid-catalyzed breakdown of carbinolamines to semicarbazones; as pointed out by these authors, secondary isotope effects indicate little or no bond rehybridization toward the sp2 carbon atom in the transition state, in contrast to p values, which support a large degree of carbon-oxygen bond cleavage in the transition state. An examination of the correlation between electronic substituent effects and secondary isotope effects for the addition of nucleophiles to aldehydes under a variety of experimental conditions would provide important reference information toward the interpretation of the data in the yeast alcohol dehydrogenase reaction.3 A comparison of structure-reactivity correlations in the horse liver alcohol dehydrogenase to the yeast enzyme indicates a similar (possibly identical) distribution of charge at C-l of substrate in the transition state (Hardman et al, 1974). Although «-secondary isotope effects have not yet been reported for the horse liver system, measurement of these effects would provide a subtle test of the extent to which transitionstate structure has been conserved among enzymes from divergent evolutionary sources catalyzing the same reaction.…”
Section: Discussionmentioning
confidence: 99%